Urban Art and Civic Learning: Bloom’s Taxonomy Applied to Quality of Life in Three Spanish Cities - Ros-García, Juan Manuel; Gutiérrez-Corregidor, Samuel; Sarasola-Rubio, Fátima (Arte, Individuo y Sociedad, 2026)
Using a comparative approach, this study examines urban art in public space as an experience of civic learning and its relationship with perceived quality of life. The Spanish urban contexts of Pamplona, Madrid, and Ceuta are analysed, selected for their relative positions (higher, intermediate, and lower) in the Multidimensional Quality of Life Indicator published annually by Spain’s National Statistics Institute (INE). The research project to which this contribution belongs is organised in two phases: (1) an inventory, geolocation, and characterisation sheets of existing artworks, linking each intervention to its urban context; and (2) the administration of a citizen survey structured around the cognitive levels of Bloom’s Taxonomy, incorporating affective and operational dimensions. Survey results across the three cities show high visibility and recognition of artistic interventions and a predominantly positive appraisal of their influence on everyday life, although active public involvement in artistic projects remains at lower levels. As a methodological contribution, the study proposes a six-item synthetic version, applicable to mediation and social-impact processes, aimed at estimating the intensity of cognitive interaction between citizens and urban art.